PREFERENSI KONSUMEN TERHADAP PEMBELIAN CABAI BESAR DI KABUPATEN SUKOHARJO - Waskito, Naufal Pratama Widya; Riptanti, Erlyna Wida; Adi, R. Kunto (LPPM Universitas Malikussaleh - Indonesia, 2023)
Chili consumption is projected to continue to increase every year along with the increasing population in Indonesia, this is an opportunity for farming. Farmers responded to this by increasing chili production. The purpose of the study was to determine the preferences and attributes that consumers consider the most towards the purchase of large chilies. The basic research method is descriptive analytic. The research locations were chosen purposively in three sub-districts in Sukoharjo Regency, namely Sukoharjo, Kartasura, and Grogol sub-districts. Sampling was done by accidental sampling totaling 100 respondents. Data analysis used Chi-Square and Fishbein Multi-attribute methods. The results showed that the large chilies that became the preference were large chilies, bright red in color because consumers considered red to be perfect ripeness, had a glossy skin surface that represented the level of freshness, had thick skin, had a very spicy level of spiciness, and had a low price. The attributes that were considered the most in succession were skin surface, skin thickness, price of chili, type of chili, skin color, and level of spiciness. Recommendations that can be given are the use of varieties that suit consumer tastes such as IPB CH3 and IPB CH6 and maintain the quality of red chilies to maintain consumer trust.